Предмет: Алгебра,
автор: playgoglecom98
2(х – 6) + 4 х = 5х – (8 +х).
Ответы
Автор ответа:
0
Ответ:
2x - 12 + 4x = 5x - (8+x)
2x - 12 + 4x = 5x - 8 - x
6x - 12 = 4x - 8
6x - 4x = -8 + 12
2x = 4
x = 2
Автор ответа:
0
2x-12+4x=5x-8-x
2x-12+4x-5x+8+x=0
2x-4=0
2x=4
x=2
2x-12+4x-5x+8+x=0
2x-4=0
2x=4
x=2
Похожие вопросы
Предмет: Другие предметы,
автор: ak47bkmz99
Предмет: Қазақ тiлi,
автор: 1985174
Предмет: Русский язык,
автор: golovina2005
Предмет: Физика,
автор: sprogamer40
Предмет: Математика,
автор: llilul